2013
DOI: 10.2141/jpsa.0120118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Dose Daidzein on Laying Performance, Egg Quality and Antioxidation in Laying Hens

Abstract: This trial was conducted to evaluate the effects of high-dose daidzein supplements on laying performance, egg quality and antioxidation in laying hens during the late laying period. Seven hundred sixty eight 55-wk-old Hyline Brown were randomly assigned to four groups with 8 replicates of 24 birds each (192 laying hens per group) and fed diets supplemented with 0 (control), 10 mg/kg, 50 mg/kg and 100 mg/kg daidzein for 8 wk in the diets. Egg production, egg mass, feed conversion and egg yolk malondialdehyde we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
9
0
2
Order By: Relevance
“…For instance, chitosan oligosaccharide was found to improve the antioxidant status and metabolic pro les of amniotic uid, which subsequently improved the foetal survival and growth in a pig model [33]. Daidzein is a class of avonoid compounds with estrogen properties and has been reported to have a potential effect on animal reproductive capacity [34][35][36]. In the present study, DAI supplementation signi cantly increased the number of viable embryos at 35 dg.…”
Section: Discussionsupporting
confidence: 50%
“…For instance, chitosan oligosaccharide was found to improve the antioxidant status and metabolic pro les of amniotic uid, which subsequently improved the foetal survival and growth in a pig model [33]. Daidzein is a class of avonoid compounds with estrogen properties and has been reported to have a potential effect on animal reproductive capacity [34][35][36]. In the present study, DAI supplementation signi cantly increased the number of viable embryos at 35 dg.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, multiparous sows have been supplemented with dietary daidzein of 1 mg/kg body weight per day during late gestation, which could affect meat quality and skeletal muscle cellularity of the multiparous sow’s offspring [ 5 ]. Concerning poultry subjects, there have also been studies that have shown that daidzein could be a very effective additive to improve laying performance, eggshell quality and egg yolk total superoxide dismutasein in laying hens during the late laying period [ 6 ]. Another study showed that daidzein supplementation could increase egg weight and fertility, and affect serum progesterone (P4), thyroxine (T4) and growth hormone (GH) concentrations in female geese [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of daidzein, a natural isoflavonic phytoestrogen with oestrogenic activity ( Kuiper et al, 1998 ), has been studied in a variety of animal species such as rats, laying hens, female geese and sows, and breeding cows ( Liu et al., 2013 ; Zhang et al., 2018 ; Cai et al, 2013 ; Zhao et al., 2013 ; Gentao et al., 1999 ). In the present study, we found that 200 mg/kg daidzein supplementation increased the total numbers of born and born alive, as well as the total litter weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although our previous research found a potential negative effect of daidzein supplementation at an extremely high dosage on the body weight gain and splenic morphology of piglets ( Xiao et al., 2015 ), most studies using a low or moderate dosage have shown that daidzein supplementation before parturition significantly increases the litter weight and milk yield in sows ( Gentao et al., 1999 ). In addition, the effects of daidzein on the reproductive performance are closely associated with the animal species, sex, dose, and physiological status ( Zhang et al., 2018 ; Cai et al, 2013 ; Zhao et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%